Penafsiran Terhadap Galatia 6:2 Berdasarkan Teori Taksonomi Bloom dan Relevansinya Bagi Pendidikan Anak Usia Remaja - Bram M, Prionaray (Jurnal Kala Nea, 2024)
This research tries to examine Galatians 6:2 as a teaching advice that is affective teaching. This was then collaborated with the perspective of a psychologist who is involved in observations in the world of education, namely Benjamin Bloom. In the taxonomy, there are three domains of educational concepts, namely the cognitive domain, affective domain and psychomotor domain. What then becomes the core point of focus in this research is the affective domain, as a domain of teaching that shows the implementation of teachings through action. In its relevance to teenagers, as a core teaching material for Christianity, Galatians 6:2 is studied using a historical hermeneutic approach, by providing a transparency of thought regarding how teaching should be accompanied by practice, which is closely related to the realm of affective thought, a flowering taxonomy, as a completeness in education and the subject of education. As the target object are teenagers, remembering how in the order of adolescent development, this is a growth phase which can be the key to the initial foundation in forming a life commitment which must be accompanied by teaching that can be accepted and practiced in the daily lives of teenagers.